Newborn hearing screening program in China: a narrative review of the issues in screening and management - Wen, Cheng; Huang, Li-Hui (Frontiers in Pediatrics, 2023)
Hearing loss is one of the most common sensory disorders in humans. The purpose of this review was to summarize the history and current status of newborn hearing screening in China and to investigate future developmental trends in newborn hearing screening with the intention of sharing experiences and providing a reference for other populations. In the 1980s, the exploration of hearing monitoring for high-risk infants led to the gradual development of newborn hearing screening in China. With the continuous improvement of screening technology, the newborn hearing screening program was gradually extended to the whole country and became a government-led multidisciplinary public health program. Genetic screening for deafness has been incorporated into newborn hearing screening in many regions of China to help screen for potential and late-onset deafness in newborns. In the future, it is necessary to further establish and improve whole life-cycle hearing screening and health care, conduct screening for congenital cytomegalovirus infection, and create a full-coverage, whole-life hearing screening and intervention system. Conclusions: Screening for deafness in China has been marked by 40 years of achievements, which have been a source of pride for entrepreneurs and comfort for patients and their families. It is important to manage hearing screening data information more efficiently and establish a quality control index system throughout the whole screening process. Genetic screening for concurrent newborn hearing and deafness has great clinical importance for the management of congenital deafness and prevention of ototoxicity. A whole life course hearing screening and intervention system should be developed.